Spatial dimensions of scheduled castes in India - "Chandna, R. C." (New Delhi, 1989)
The scheduled castes in India accounting for about one-seventh population of the country play a significant role in the country's society, economy and polity. However, despite repeated proclamations from official as well as non-official platforms about the constitutional provisions for the upliftment of this segment of Indian society, most of them continue to suffer the same living conditions which their previous generations had suffered. The present volume is a pioneer geographic effort to analyse all their characteristics in the context of aggregate nature places of their occupance. The study is based upon the vast treasure of data published by the Census of India covering all such attributes as distribution, growth. migration, sex composition, literacy, working force, occupational structure and incidence of urban living. It is for the first time that the country's scheduled caste population statistics have been subjected to such an exhaustive analysis by a geographer. The massive district wise information published by the Census of India has been represented cartographically on a number of plates. The spatial patterns as emerging on these plates have been discussed in detail. Apart from the spatial differences, the inter-caste differences among the scheduled castes themselves have seussed wherever relevant. The find study are of immense utility in the amelioration of the people belong the scheduled castes in different parts of the country.
Keywords: Untouchables-India